Perbandingan Jumlah Leukosit pada Anak yang Menderita DBD dengan Syok dan tanpa Syok di RSUD Dr H Chasan Boesoirie Ternate Periode Januari-Desember 2020 - Jihan Ichsan; Husain Assagaf; Eko Sudarmo D Prihanto (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2022)
Dengue hemorrhagic fever (DHF), a dengue virus infection transmitted by Aedes aegypti mosquito, has become one of the main global diseases. White blood cell count is one of laboratory parameters examined on DHF with daily variation. The purpose is to identify the white blood cell count comparison between pediatric DHF patient with and without shock  based on the day of illness. On this retrospective cross-sectional analytic study, the study subjects were DHF patients aged 1-17 years old with and without shock according to the WHO 2011 criteria. Secondary data was obtained from medical record of patients admitted in the pediatric ward, dr H Chasan Boesoirie General Hospital, in January-December 2020. The Mann-Whitney statistical test was utilized to analyze white blood cell count and patient's characteristics The white blood cell average count of DHF patients with shock decreased on day 3 of illness, reached the lowest point on day 4 of illness (2220/mm3) and increased on day 5 of illness (6585/mm3). The white blood cell average count of DHF patients without shock tends to be stable day by day. Regarding the while blood cell count comparison between DHF with and without shock patients, statistical significance was only identified on fever day 6 (p=0,026). So, there was a significant difference of average white blood cell count of DHF with and without shock on day 6 of illness. . Keywords: Dengue Hemorrhagic Fever, Shock, White Blood Cell.